Elongation of Long‐Chain Fatty Acid Family Member 6 (Elovl6)‐Driven Fatty Acid Metabolism Regulates Vascular Smooth Muscle Cell Phenotype Through AMP‐Activated Protein Kinase/Krüppel‐Like Factor 4 (AMPK/KLF4) Signaling - Hiroaki Sunaga; Hiroki Matsui; Saki Anjo; Mas Risky A. A. Syamsunarno; Norimichi Koitabashi; Tatsuya Iso; Takashi Matsuzaka; Hitoshi Shimano; Tomoyuki Yokoyama; Masahiko Kurabayashi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
Background Fatty acids constitute the critical components of cell structure and function, and dysregulation of fatty acid composition may exert diverging vascular effects including proliferation, migration, and differentiation of vascular smooth muscle cells (VSMCs). However, direct evidence for this hypothesis has been lacking. We investigated the role of elongation of long‐chain fatty acid member 6 (Elovl6), a rate‐limiting enzyme catalyzing the elongation of saturated and monounsaturated long‐chain fatty acid, in the regulation of phenotypic switching of VSMC. Methods and Results Neointima formation following wire injury was markedly inhibited in Elovl6‐null (Elovl6−/−) mice, and cultured VSMCs with siRNA‐mediated knockdown of Elovl6 was barely responsive to PDGF‐BB. Elovl6 inhibition induced cell cycle suppressors p53 and p21 and reduced the mammalian targets of rapamycin (mTOR) phosphorylation and VSMC marker expression. These changes are ascribed to increased palmitate levels and reduced oleate levels, changes that lead to reactive oxygen species (ROS) production and resulting AMP‐activated protein kinase (AMPK) activation. Notably, Elovl6 inhibition robustly induced the pluripotency gene Krüppel‐like factor 4 (KLF4) expression in VSMC, and KLF4 knockdown significantly attenuated AMPK‐induced phenotypic switching of VSMC, indicating that KLF4 is a bona fide target of AMPK. Conclusions We demonstrate for the first time that dysregulation of Elovl6‐driven long‐chain fatty acid metabolism induces phenotypic switching of VSMC via ROS production and AMPK/KLF4 signaling that leads to growth arrest and downregulation of VSMC marker expression. The modulation of Elovl6‐mediated cellular processes may provide an intriguing approach for tackling atherosclerosis and postangioplasty restenosis.